KAJIAN DANA DALAM SUTTAPITAKA - Ida Yati; Julia Surya; Dewi Astuti; Pedi Kurniawan; Ria Astika (Dharmasmrti: Jurnal Ilmu Agama dan Kebudayaan, 2024)
This article was written with the aim of understanding the concept of fund based on the suttas. In this article we will discuss the concept of good giving, to whom the right funds are given, the right time to give funds, good forms of funds, and how funds become an initial maintenance practice for married people. The practice of giving is important, because if it is done with true belief and sincerity, it will reduce attachment and greed within oneself.